The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14122487
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Induces Subtle Histological Changes in Duodenal Mucosa of Patients with Non-Coeliac Gluten Sensitivity: A Multicentre Study

Abstract: Background: Histological changes induced by gluten in the duodenal mucosa of patients with non-coeliac gluten sensitivity (NCGS) are poorly defined. Objectives: To evaluate the structural and inflammatory features of NCGS compared to controls and coeliac disease (CeD) with milder enteropathy (Marsh I-II). Methods: Well-oriented biopsies of 262 control cases with normal gastroscopy and histologic findings, 261 CeD, and 175 NCGS biopsies from 9 contributing countries were examined. Villus height (VH, in μm), cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
2
14
1
1
Order By: Relevance
“…In these types of studies, considering gluten responsiveness as a defining feature of CD, clinical researchers try to evaluate the patients’ response to different amounts of gluten, and their results can be considered vital for both patient care and clinical trial designs. However, due to a lack of standardization of important factors such as time and gluten dose, the available data are different from each other in their objectives and designs [ 44 ]. In the current study, we tried to conduct a systematic review and dose-response meta-analysis on previously published data to explore the potential of different amounts of gluten in the induction of disease relapse in patients with CD, which can be an important step in advancing CD management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these types of studies, considering gluten responsiveness as a defining feature of CD, clinical researchers try to evaluate the patients’ response to different amounts of gluten, and their results can be considered vital for both patient care and clinical trial designs. However, due to a lack of standardization of important factors such as time and gluten dose, the available data are different from each other in their objectives and designs [ 44 ]. In the current study, we tried to conduct a systematic review and dose-response meta-analysis on previously published data to explore the potential of different amounts of gluten in the induction of disease relapse in patients with CD, which can be an important step in advancing CD management.…”
Section: Discussionmentioning
confidence: 99%
“…First, the included studies implemented different approaches to evaluate disease relapse in response to gluten challenges. These approaches included evaluating patient-reported symptoms that are subjective; assessing serological biomarkers that are not sensitive enough; assessing histological damages such as Vh/Cd ratio and IEL count that allow investigators to evaluate villous blunting and lymphocyte infiltration but require assessment by a skilled pathologist [ 33 , 44 ]. The studies also differ from each other in terms of sample size, the amount of gluten administered, duration of the challenge, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The number of intra-epithelial CD3 positive T lymphocytes (IEL) was recorded. Lymphocytes were counted per 100 enterocytes covering the villous epithelium of the entire villus, as reported in [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies indicate that gliadin also contains peptides able to activate an innate immune response [ 41 , 42 , 43 ]. In the early phase of CD, epithelial cells are likely destroyed via toxic gliadin peptides, such as 19-mer [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], that might activate the innate immune system, thereby upregulating interleukin IL-15 secretion [ 44 ]. Recently, it has been found that 33-mer peptide could also activate the innate immune system via TLR-2 and TLR-4 receptors, inducing the release of pro-inflammatory cytokines, such as IP-10/CXCL10 and TNF-α ( Figure 1 a) [ 45 ].…”
Section: Gluten Componentsmentioning
confidence: 99%
“…Sapone et al, 2010 [ 7 ]; Brottveit et al, 2013 [ 17 ]; Volta et al,2012 [ 21 ]; Carroccio et al, 2012 [ 20 ]; Carroccio et al, 2019 [ 28 ]; Zanini et al, 2018 [ 25 ]; Rostami et al, 2022 [ 29 ]…”
Section: Figureunclassified